Jon Fosse på den globale scenen: En dataanalyse - Hanssen, Jens-Morten (Teatervitenskapelige studier, 2023)
During the 1990s Jon Fosse went from being a prose writer with a limited Norwegian audience to becoming a playwright with an ever-expanding global distribution. His current international standing is closely connected to the fact that he began to write dramatic texts. With a point of departure in the recently acquired Jon Fosse Archive, the National Library of Norway has established a dataset of information about all documented stage productions of Fosse’s works worldwide in collaboration with the Sceneweb Archive. This paper conducts an analysis of this dataset from three angles: geography, social structure, and organizational factors. It is no denying that Fosse has become a world dramatist, but the study shows that his distribution has a strong European bias, where three nations stand out, Norway, France, and Germany. Using social network analysis, the study identifies the major hubs in the global network of stage artists involved in producing Fosse and reveals that most of them are Norwegian or Swedish. However, these artists have engaged in transnational, artistic collaborations that over time have created a form of distributed ownership to his works. Additionally, Fosse has fared well in the system of international festivals which has further strengthened his global standing.